(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the formation of skills and abilities from the school age, especially the socio-psychological aspects of the development of creativity during the student’s childhood, is discussed in order to increase the creative competence of schoolchildren.